Organization of a pupil personnel council in a shared services project - Flanders, Robert E.; Jackson, Willathea G. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1968)
A description of the rationale and basic procedures of organizing a pupil personnel council are presented. The council should be composed of pupil personnel workers in the school system. Case conferences, consultation with administrators, and procedural decisions are among the possible activities of such a council. (ns)
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Staff Meetings; Student Personnel Services